[Suds story ; Bote garapa ; Hari ng Stunt [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Investigates the hard detergent bar as polluting the environment. Patis, toyo, bagoong are staples that come bottled in recycled gun bottles. A House bill proposes that the practice be stopped. The staple manufacturers say that recycling is well within their rights. The gin makers are up in arms against what they call a usurpation of their property rights. Features stuntmen in the movies.
Suds story (14 min.) -- Bote garapa (16 min.) -- Hari ng stunt (10 min.)
VHS.
Keywords: Soap; Bottles -- Laws and legislation. -- Philippines; Bottles -- Philippines; Refuse and refuse disposal -- Philippines; Stunt men and women -- Philippines